Legal aspects of surgical instrumentation in Colombia - Galán Camargo, Viviana (DIXI, 2020)
Subject and scope: The article analyzes how the “instrumentador quirúrgico” (Surgical assistant specializing in surgical instruments), given his academic training, is a qualified professional capable of offering comprehensively suitable and clear criteria in the various surgical procedures of the different specialties, asepsis and antisepsis management, and infection control, always acting with responsibility, with a humanistic and ethical sense, and keeping professional secrecy.Characteristics: Today we can see how the “instrumentador quirúrgico” is a leader in generating information about operating room service, the operation of sterilization plants with quality and competitiveness, in order to administer and issue technical concepts on intra-hospital equipment or externally to commercial establishments that provide similar services.Findings: The professional development of surgical instrumentation in Colombia has been a benchmark for Latin America.Conclusions: The “instrumentador quirúrgico” must treat each patient humanely according to a reasonably supported hierarchy of their biological, psychological, social and spiritual needs.
Keywords: bioethics; Social State of Law; ethics; surgical instrument; principles; values